2020
DOI: 10.5296/ijhrs.v10i2.17085
|View full text |Cite
|
Sign up to set email alerts
|

Planning Competency in the New Normal– Employability Competency in Post- COVID-19 Pandemic

Abstract: This paper explores requirements of employability competency in the new normal; an era expected post- the COVID-19 pandemic. The research conceptualises and integrates approaches that would address how to prepare individuals for times of uncertainties, changes and challenges they most probably would face during the new normal.A framework for employability competency during new normal is proposed, followed by a toolkit that ensures we stay resilient to meet the variety of demands and the conditions expected dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 13 publications
1
65
0
9
Order By: Relevance
“…In order to ensure that an individual or his/her family would be from the concrete-middle class, their capacity should be tested to withstand the current world emergency crisis of COVID-19 pandemic and its coming spillovers. Buheji et al (2020).…”
Section: The Changes In the Concrete-middle Classmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to ensure that an individual or his/her family would be from the concrete-middle class, their capacity should be tested to withstand the current world emergency crisis of COVID-19 pandemic and its coming spillovers. Buheji et al (2020).…”
Section: The Changes In the Concrete-middle Classmentioning
confidence: 99%
“…Before COVID-19 pandemic, the majority of the world's population (56%) continued to live a low-income existence, compared with just 13% that could be considered middle income by a global standard, according to a new Pew Research Center (2020) report. Buheji et al (2020).…”
Section: The Characteristics Of the Millennium Middle Classmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 Pandemic has bought devastating effects to businesses across the globe (Buheji & Buheji, 2020). Ranging from employee outcomes to corporate goal achievement, the world witnessed tragic results.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, what scholars have recently asserted also supports our claim, encouraging organizations to utilize coaching during COVID-19 Pandemic (Utterback et al, 2020). Furthermore, Buheji and Buheji (2020) also indicated that coaching alongside training could help cope with the changing demands and situation during and after the COVID-19 crisis.…”
Section: Introductionmentioning
confidence: 99%